Analysis of the relationship between the quality of antenatal care examinations and the incidence of preterm birth and low birth weight - Hu Wenling; Di Jiangli; Huang Aiqun; Zhao Wei; Hu Huanqing; Chen Sidi (BMC Public Health, 2024)
Abstract Background Antenatal care (ANC) plays a crucial role in ensuring maternal and child safety and reducing adverse delivery outcomes. This study aimed to analyze the association between the quality of ANC and the occurrence of preterm birth and low birth weight in a sample of the population from 16 regions in 8 provinces in China. Methods Data from all closed cases of pregnant women and newborns reported in the Maternal and Child Health Monitoring System from January 1, 2018, to December 31, 2018, in 16 monitoring regions across 8 provinces in China were collected and included in the analysis, resulting in a total of 49,084 pregnant women and 49,026 newborns. Results The mean number of ANC visits was 6.95 ± 3.45. By percentage, 78.79% of the women received ANC examinations at least five times. The percentage of normative ANC examinations and the percentage of qualified ANC examinations was 30.98% and 8.0% respectively. The gestational age(χ2 = 229.305, p<0.001), birth weight (χ 2  = 171.990, p<0.001) and the occurrence of neonatal complications (χ 2  = 53.112, p<0.001) were all significantly related to the number of ANC visits to mothers. There was a correlation between gestational age (χ 2  = 1021.362, p<0.001;χ 2  = 194.931, p<0.001) and birth weight (χ 2  = 259.009, p<0.001; χ 2  = 70.042, p<0.001) with normative ANC and qualified ANC examinations. As the number of ANC examinations increased, the rates of preterm birth and low birth weight decreased. Pregnant women who did not receive normative ANC examinations had a higher risk of preterm birth and neonatal low birth weight compared to those who did; Adjusted Odds Ratio (95%CI) was 23.33(16.97~32.07)and 1.61(1.37~1.90) respectively. Pregnant women who did not receive qualified ANC examinations had a higher risk of preterm birth and neonatal low birth weight compared to those who did; Adjusted Odds Ratio (95%CI) was 15.05(8.45~26.79)and 1.36 (1.02~1.82) respectively. Conclusion The percentage of women who received normative ANC examination and qualified ANC examination is still low in China, and the quality of antenatal care significantly affects the occurrence of preterm birth and low birth weight in newborns.